Analysis of Myxococcus xanthus Vegetative Biofilms With Microtiter Plates - Dye, Keane J.; Yang, Zhaomin (Frontiers in Microbiology, 2022)
The bacterium Myxococcus xanthus forms both developmental and vegetative types of biofilms. While the former has been studied on both agar plates and submerged surfaces, the latter has been investigated predominantly on agar surfaces as swarming colonies. Here we describe the development of a microplate-based assay for the submerged biofilms of M. xanthus under vegetative conditions. We examined the impacts of inoculation, aeration, and temperature to optimize the conditions for the assay. Aeration was observed to be critical for the effective development of submerged biofilms by M. xanthus, an obligate aerobic bacterium. In addition, temperature plays an important role in the development of M. xanthus submerged biofilms. It is well established that the formation of submerged biofilms by many bacteria requires both exopolysaccharide (EPS) and the type IV pilus (T4P). EPS constitutes part of the biofilm matrix that maintains and organizes bacterial biofilms while the T4P facilitates surface attachment as adhesins. For validation, we used our biofilm assay to examine a multitude of M. xanthus strains with various EPS and T4P phenotypes. The results indicate that the levels of EPS, but not of piliation, positively correlate with submerged biofilm formation in M. xanthus.